Generalized hierarchical cyclic pursuit. (September 2016) - Mukherjee, Dwaipayan; Ghose, Debasish
Abstract: Cyclic pursuit has been an important connection topology in multi-agent systems. Many variants of the classical cyclic pursuit law have been analysed by researchers. Among these variants are homogeneous and heterogeneous cyclic pursuit, or single layer and hierarchical cyclic pursuit. In this paper hierarchical cyclic pursuit, with heterogeneous gains, has been considered. This paper generalizes existing results by allowing both heterogeneity in the gains, and extension of the single layer information flow graph to a multi-layer hierarchical structure. Some new results are presented about the reachability of agents in hierarchical cyclic pursuit. It is shown that the existing results may be obtained as special cases of the results obtained in this paper. Simulation results are provided to support the theoretical findings.